A comparison of the Kalburcayiri lignites in the Kangal-Sivas basin and various worldwide coal compositions - Kalender, Leyla; Karamazi, Kevser (Inderscience Enterprises Ltd, 2017)
The objective of this study is to compare the composition of the major, trace and rare earth element (REE) of the Kalburcayiri lignites in the Kangal basin with the compositions of worldwide coals. It is clear that Mo, Zn, Ni, As, U, Sr, Sb, V, Cr, Cs, Se and Tl in the Kalburcayiri lignites are the highest coalphile elements (coal affinity index > 5) in both the surface and drill core lignite samples. The greater coal affinity index values may be implied contribution of an authigenic fraction on the trace element concentrations. It should be taken into consideration that the Kalburcayiri lignites contain radioactive elements such as U, Re, and Cs due to Turkish type volcanic input, these are carcinogen substances and may have negative effect on the human health and environment via earth, water and air.
Keywords: geochemistry; lignites; Kalburcayiri; Sivas; Turkey